Arc Hydro Hillslope and Critical Duration: New tools for hillslope-scale runoff analysis. (July 2022) - Lapides, Dana; Sytsma, Anneliese; O'Neil, Gina; Djokic, Dean; Nichols, Mary; Thompson, Sally
Abstract: Hillslopes are a fundamental unit of surface hydrology, mediating the flow of water to fluvial networks through overland flow and subsurface pathways. We present Arc Hydro tools to delineate hillslope outlines, identify hillslope width functions and implement an overland flow model that accounts for hillslope curvature. We apply the new tool to subwatersheds in the Walnut Gulch Experimental Watershed and Las Trampas Creek Watershed to investigate properties of hillslope curvature and impact of curvature on peak flows. We found that, for these two subwatersheds, divergent, convergent, and uniform-width hillslopes account for 43%, 55%, and 2% of subwatershed areas, respectively. This curvature is substantial enough to increase peak flow predictions by up to a factor of 3 on some hillslopes, and can be exaggerated at larger scales as multiple hillslope hydrographs are superimposed. Our findings suggest that hillslope curvature may play an important role in hydrological processes on real landscapes.